Incidence Patterns of Pediatric and Adolescent Orthopaedic Fractures According to Age Groups and Seasons in South Korea: A Population-Based Study - Park, Moon Seok (The Korean Orthopaedic Association, 2013)
BACKGROUND: Fractures which need urgent or emergency treatment are common in children and adolescents. This study investigated the incidence patterns of pediatric and adolescent orthopaedic fractures according to age groups and seasons in South Korea based on population data. METHODS: Data on the number of pediatric and adolescent patients under the age of 18 years who utilized medical services due to fractures were retrieved from the Health Insurance Review and Assessment service in South Korea. The data included four upper extremity and two lower extremity fractures according to four age groups (0-4 years, 5-9 years, 10-14 years, and 15-18 years). Incidences of the fractures were calculated as the incidence per 10,000 per year, and patterns according to age groups and seasons were demonstrated. RESULTS: The annual incidence of clavicle, distal humerus, both forearm bone, distal radius, femoral shaft and tibial shaft fractures were 27.5, 34.6, 7.7, 80.1, 2.5, and 9.6 per 10,000 per year in children and adolescents, respectively. Clavicle and distal radius fractures showed significant seasonal variation for all age groups but femoral shaft fracture showed no significant seasonal variation for any of the age groups. CONCLUSIONS: The four upper extremity fractures tended to show greater variations than the two lower extremity fractures in the nationwide database in South Korea. The study results are believed to be helpful in the planning and assignment of medical resources for fracture management in children and adolescents.